1959
DOI: 10.1161/01.cir.20.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prolonged Use of Estrogens on Circulating Lipids in Patients with Idiopathic Hyperlipemia or Idiopathic Hypercholesteremia

Abstract: The low incidence of atherosclerosis in premnenopausal woomen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1961
1961
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The present treatment regimen provided an opportunity to study effects of increasing doses over 3 log units without appreciable differences in the metabolic parameters measured. Other studies indicated a lipid-lowering effect, with disappearance of xanthomas when estrogens were administered to hyperlipidemic subjects (20). The cholesterol effects in the present study may be related to the significantly lower pretreatment.…”
Section: Discussionsupporting
confidence: 50%
“…The present treatment regimen provided an opportunity to study effects of increasing doses over 3 log units without appreciable differences in the metabolic parameters measured. Other studies indicated a lipid-lowering effect, with disappearance of xanthomas when estrogens were administered to hyperlipidemic subjects (20). The cholesterol effects in the present study may be related to the significantly lower pretreatment.…”
Section: Discussionsupporting
confidence: 50%
“…In addition to the marked reduction in serum lipid and lipoprotein values, striking disappearance of xanthomatous lesions has been induced by means of oral estrogen therapy in patients with primary hypercholesterolemia xanthomatosis and idiopathic hyperlipemia (17, 78).…”
Section: Other Pertinent Metabolic and Endocrine Effects Of Estrogensmentioning
confidence: 99%
“…Prolonged administration of estrogens does not appear to lessen this metabolic effect, and no tolerance or resistance to the hormone has been observed (66). In addition to the marked reduction in serum lipid and lipoprotein concentrations, striking disappearance of xanthomatous lesions has been induced by oral estrogen therapy in patients with primary hypercholesterolemic xanthomatosis or idiopathic hyperlipemia (75–77). Relatively small doses of methyltestosterone can counteract completely the biochemical effects of estrogens when the two are administered simultaneously (75).…”
Section: Discussionmentioning
confidence: 99%